A new species of Dicranophora Macquart (Diptera, Stratiomyidae) from Bahia State, Brazil and a key to species of the genus - de Godoi, Fabio Siqueira Pitaluga; Rafael, José Albertino (Zootaxa, 2013)
A new species of the Neotropical Dicranophora Macquart is described and illustrated from six males collected in north-east Brazil, Bahia state (Encruzilhada district). Dicranophora femurspiculata sp. nov. is characterized by the specific pat-tern of spots on the frons, on the legs and on the abdomen, and by a distinct shape of the scutellar process and mid femur. A key to the species of the genus and a distribution map are presented.